2002
DOI: 10.1046/j.1440-1681.2002.03671.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect Of T‐1095, A Selective Inhibitor Of Renal Na+–Glucose Cotransporters, On Metabolic Index And Insulin Secretion In Spontaneously Diabetic Gk Rats

Abstract: 1. To investigate the pharmacological effects of T-1095, this novel derivative of phlorizin was administered to GK rats for 8 weeks. T-1095 treatment significantly lowered plasma glucose and glycosylated haemoglobin (HbA1c) levels, but did not significantly affect bodyweight. 2. T-1095 treatment did not affect 3.3 mmol/L glucose-induced insulin secretion in the isolated perfused pancreas of GK rats. 3. The peak insulin release in T-1095-treated GK rats was significantly higher during the first phase than in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In this sense, this SGLT2 inhibitor offers some advantages over existing antidiabetic drugs such as sulfonylureas, biguanides, ␣-glucosidase inhibitors, and thiazolidinediones. Multiple studies on T-1095 have demonstrated its beneficial effects on postprandial hyperglycemia, FPG, GHb, insulin resistance, ␤-cell function, and diabetic complications (nephropathy and neuropathy) in diabetic rodent models (Adachi et al, 2000;Nawano et al, 2000;Oku et al, 2000;Arakawa et al, 2001;Nunoi et al, 2002;Ueta et al, 2005;Fujimoto et al, 2006). We suppose that remogliflozin etabonate may also be useful for a wide range of diabetic conditions, and it can be beneficial for the treatment of diabetes when used in combination with a number of antidiabetic drugs.…”
Section: Discussionmentioning
confidence: 94%
“…In this sense, this SGLT2 inhibitor offers some advantages over existing antidiabetic drugs such as sulfonylureas, biguanides, ␣-glucosidase inhibitors, and thiazolidinediones. Multiple studies on T-1095 have demonstrated its beneficial effects on postprandial hyperglycemia, FPG, GHb, insulin resistance, ␤-cell function, and diabetic complications (nephropathy and neuropathy) in diabetic rodent models (Adachi et al, 2000;Nawano et al, 2000;Oku et al, 2000;Arakawa et al, 2001;Nunoi et al, 2002;Ueta et al, 2005;Fujimoto et al, 2006). We suppose that remogliflozin etabonate may also be useful for a wide range of diabetic conditions, and it can be beneficial for the treatment of diabetes when used in combination with a number of antidiabetic drugs.…”
Section: Discussionmentioning
confidence: 94%
“…Chronic treatment with T-1095 reduces glucose and glycohemoglobin levels, lowers insulin and triglyceride levels, normalizes whole body and muscle GLUT 4 content, and decreases hepatic glucose production [62]. They also describe a number of renal effects of T-1095 in animal models of diabetes, including delay in the development of microalbuminuria, normalization of renal GLUT 2 levels, restoration of normal kidney weight and epithelial vacuolation [63][64][65][66].…”
Section: Phlorizin Pharmacologymentioning
confidence: 99%
“…19 The O-glycoside 3a (T-1095A) exhibited sufficiently promising potency, selectivity, and in vivo efficacy when administered orally, if protected from intestinal glucosidases, that it entered clinical trials as the methyl carbonate prodrug 3b (T-1095). [20][21][22] The report from Wyeth that administration of 4-benzylpyrazolones 4, such as 4a (WAY-123783), could induce a glucosuric response in mice prompted investigations at Kissei and Bristol-Myers Squibb that independently led to the realization that in vivo glucosylation of 4 must occur to generate a series of potent SGLT2 inhibitors 5. 23 Subsequently, merging of structures 3 and 5 and truncation of the tether joining the two aryl rings of phlorizin from three carbons to one carbon by chemists at Bristol-Myers Squibb and Kissei independently led to disclosure of O-glucosides of o-benzylphenols 6 as a second potent series of SGLT2 inhibitors ( Figure 3).…”
Section: Sglt2-selective O-glucosidesmentioning
confidence: 99%
“…[18][19][20][21][22]26 The in vivo profile of 16 suggests that C-glucoside based inhibitors are no different. When administered at 0.1-1.0 mg/kg to normal and diabetic rats, 16 dose- dependently increased glucosuria, resulting in urinary glucose excretion of up to 1.0 g/day without causing hypoglycemia.…”
Section: Preclinical In Viwo Studiesmentioning
confidence: 99%